Review of phase I and II trials for Wilms' tumour – Can we optimise the search for novel agents?. (July 2017) - Brok, Jesper; Pritchard-Jones, Kathy; Geller, James I.; Spreafico, Filippo
Abstract: Survival rates for patients with Wilms' tumour (WT) approximate 90% with refined use of currently available interventions. However, a subgroup of patients, with initial high-risk histopathology or relapsing disease, have a poor prognosis, and it is a challenge to identify and prioritise the development of new innovative approaches for these subgroups. We conducted a systematic literature search for published phase I and II clinical trials that registered patients with WTs and characterised the early phase trial activity, quantified response rates and highlighted avenues for further development. We identified 63 trials (48 phase I, three phase I/II, and 12 phase II trials) enrolling 214 patients with WTs, alongside other malignancies. The number of annually recruited WTs did not change significantly and was less than 20% of the potential candidates. The vast majority of the trials were conducted in North America, and 56 different interventions were investigated, including conventional chemotherapy and biologically targeted therapies. Overall, 33 WTs revealed some degree of tumour control. Of these, five patients demonstrated complete remission (2%), 15 patients partial response (7%) and 13 patients stable disease (6%). None of the included novel biologically targeted therapies emerged as promising interventions, and only conventional chemotherapy was able to induce a complete and partial response. We conclude that early phase trial recruitment of WTs is below expected levels, and the clinical outcome of the included patients is dismal. Improvement of the availability and recruitment to early phase trials for WTs, especially in Europe, is needed. Highlights: Recruitment of relapsed patients with Wilms' tumour in early phase trials seems below expected levels. The clinical outcome of patients with Wilms' tumour in early phase trials is dismal. Improved availability of early phase trials and optimisation of recruitment for Wilms' tumour, especially in Europe, is needed.